Comments on ADHD in youth and adult education: a mini review. (Research, Society and Development, 2021)
Attention deficit disorder [ADHD] is considered a problem that occurs mainly in children and that makes life difficult for the student due to the lack of understanding of the problem by the teachers and the family of the individual affected by this disorder, which generates behavioral and social life l problems. Social living. This problem can persist in adults and, in addition to being neglected in children and young people, it is even more in adults. Within this scope, this systematic review was carried out to verify and to alert about ADHD in adults and the problems that affect college students who suffer from this disorder. In conclusion, it was found that ADHD in adults is, in fact, neglected and that problems in social relationships and with teachers affect academic activities and that university professors, in general, especially those who do not have pedagogical training, are not prepared to understand the situation that affected the students, which can lead to school dropout and psychological problems more serious than ADHD itself.